Urban park pathways' design and their influence on pedestrian preference; a case study in Ipoh, Perak / Razlin Rais and Sufian Che Amat - Rais, Razlin; Che Amat, Sufian (2019)
According to the United Nation, almost 60% of the world population will live in urban areas by the year 2030. As the city grows and urbanizes, green public spaces are needed for better quality of life for city dwellers. Similarly, urban public parks are not a strange term for the city of Ipoh dwellers and they play a big role in improving the city's environmental, social and economic wellbeing. A number of public parks were created and landscaped beautifully in the heart of Ipoh such as Bandar Seri Botani Eco Park and DR Seenivasagam Recreation Park for the purpose of recreational and family activities. In addition, pedestrian pathways were also widely built in parks for users' convenience. However, it has been observed that quite often visitors to these public parks often prefer to crisscross along alternative impromptu pathways whilst the original intended footpaths remain underutilised and can often be seen as surplus. This paper reviews the various environmental and social reasons that may have influenced users and visitors to the public parks in the city of Ipoh.